Experimental measurement of squeeze flow in bearings - Mak, Weng Keong. (2011)
This project investigates the squeeze film effects of bearings with spiral groove design at various fluid film thicknesses and different rotational speeds. From literature, it is known that spiral grooves on the surface of a spiral groove bearing generate pressure rise along the radius of the flat surface of the bearing, enhancing its load carrying capacity. Thus experimental investigations were carried out for two similar spiral groove bearings with different number of grooves in two types of experiments. Parameters for the geometry used in the two spiral groove bearings are based on the parameters suggested in literature. In the first series of tests, the two extended spiral groove bearings were tested using a closed system with no transverse flow. Pressure generations and temperature variations arising from different rotational speeds and four different film thicknesses were examined. In the second series of tests, the same two extended spiral groove bearings were tested using an open system with transverse flow. In the second series of tests, apart from pressure generations and temperature variations, the change in flow rate was also recorded for different rotational speeds and three different film thicknesses. It was found that in both series of tests, pressure generation and change in flow rate tended to be greater at smaller fluid film thicknesses. Also, it was found that pressure generation and inwardly pumping capability of the spiral groove bearing is lost at larger film thicknesses and higher rotational speeds.